GLOBAL COOPERATION AS A CONDITION FOR SUSTAINABLE ECONOMIC PROGRESS (INNOVATIVE ECONOMY, 2025)
Ivashchuk I.O., Zapukhlyak V.Z. GLOBAL COOPERATION AS A CONDITION FOR SUSTAINABLE ECONOMIC PROGRESSPurpose. Theoretical conceptualization of global cooperation, justification of its role in ensuring sustainable economic progress, and construction of a multi-vector strategic model of global cooperation.Methodology of research. In order to achieve the set goal, a combination of methods was used in the research process: induction and deduction – to formulate theoretical provisions of global cooperation; analysis and synthesis – to identify the main forms of international interaction and key challenges to global cooperation; comparative method – to identify current trends in global cooperation; scenario analysis – to form strategic vectors of global cooperation and determine their impact on achieving economic progress; economic and statistical analysis – to assess the dynamics of global interaction indicators and economic progress.Findings. It is argued that global cooperation is a strategic prerequisite for ensuring sustainable economic progress. The forms of international interaction through which countries integrate into the global space are outlined, and the differences between global cooperation and other related terms are analyzed. A system of principles of global cooperation is defined. The dynamics of the main areas of global cooperation are assessed. Strategic vectors of international cooperation are proposed: Openness and Growth, Sustainability and Security, Inclusive Governance and Legitimacy. It has been established that the understanding of openness is changing under the influence of financial and security factors, which is confirmed by an analysis of the dynamics of trade openness and the identification of influencing factors at different stages of development. Particular attention is paid to the impact of sanctions on economic progress. The impact of strategic vectors of global cooperation on economic progress is detailed. The prospects for the development of global cooperation and its latest forms are identified, with an emphasis on digital diplomacy, which contributes to sustainable economic progress.Originality. The theoretical conceptualization of global cooperation has been further developed, which has made it possible to propose the author's interpretation of this concept, identify its types and principles, and justify its role in ensuring sustainable economic progress. A comprehensive approach to the formation of a global cooperation strategy has been proposed, on the basis of which three strategic vectors have been identified and their impact on the achievement of economic progress has been substantiated.Practical value. The results of the study are of practical importance, in particular, the proposed three-vector strategy for global cooperation and the algorithm for selecting priorities can be used by both government authorities and business representatives to adapt the model to operating conditions, as well as in scientific and educational practice.Key words: global cooperation, economic integration, sustainable economic progress, economic growth, international trade, trade openness, global supply chains, digital diplomacy, digital trade in services, sanctions.
Keywords: global cooperation; economic integration; sustainable economic progress; economic growth; international trade; trade openness; global supply chains; digital diplomacy; digital trade in services; sanctions